2021
DOI: 10.1101/2021.04.02.438243
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roads as ecological traps for giant anteaters

Abstract: Wildlife-vehicle collisions (WVC) represent a serious source of mortality for many species, threatening local populations' persistence while also carrying a high economic and human safety cost. Animals may adapt their behaviour to road associated threats, but roadside resources can act as attractants, providing misleading signals about the quality of roadside habitats, ultimately acting as an ecological trap. Yet, the extent to which individuals modify their behaviour and space use to roads is largely unknown … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For our calculations, we did not consider the dispersal periods but included the data of the two anteaters that settled in new territories (1 month after stopping the dispersal). Previous research showed that there are no significant differences in habitat between roadsides or across roads (Noonan et al, 2021). Estimates of survival were performed using the Kaplan-Meier estimator (Rich et al, 2010) through the R package ‘survival’ (Therneau, 2021).…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…For our calculations, we did not consider the dispersal periods but included the data of the two anteaters that settled in new territories (1 month after stopping the dispersal). Previous research showed that there are no significant differences in habitat between roadsides or across roads (Noonan et al, 2021). Estimates of survival were performed using the Kaplan-Meier estimator (Rich et al, 2010) through the R package ‘survival’ (Therneau, 2021).…”
Section: Methodsmentioning
confidence: 98%
“…3350 in the west section (Fig. 1B) and 3850 in the east section (Fig.1C) (DNIT, 2020) (see for further details on study area in Ascensão et al 2021 and Noonan et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations